SEKOLAH ISLAM TERPADU PENEKANAN PADA ARSITEKTUR HIJAU DI KABUPATEN BONE - Arifin, Ismail B; Marwati, Marwati; Burhanuddin, Burhanuddin (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2014)
The development of science and technology that is integrated with the Islamic knowledge wishes to create a potential religious generation. Islamic education institution creates a religious Islamic individual through two approaches; those are natural and cultural approaches. Method that is applied is descriptive, that is collecting and analyzing the primary and secondary data. Then, planning and designing approaches are done to review various aspects oriented with architect knowledge, basic theoretic and standard. The pressure of green architecture concept enclose energy efficiency because in architect concept that is friendly environment, continuing, holistic and based on the efforts to reach designing to create energy efficiency.